Jesus and the forces of death the gospels' portrayal of ritual impurity within first-century Judaism - Thiessen, Matthew 1977- (Grand Rapids, Michigan Baker Academic, 2021)
"Correcting a popular misconception, this book demonstrates that the Gospel writers present Jesus within Judaism, opposing ritual impurity but not the Jewish law itself"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Purity, Ritual -- Judaism -- Biblical teaching; Jewish Law; Purity, Ritual -- Christianity -- Biblical teaching; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity